Cancer proteomics: from biomarker discovery to signal pathway profiling. - Bichsel VE; Liotta LA; Petricoin EF III (Cancer Journal)
In the post-genomic era of science, the field of proteomics promises the discovery of new molecular targets for therapy, biomarkers for early detection, and new endpoints for therapeutic efficacy and toxicity. Patient-specific targeted therapeutics with reduced toxicity and increased efficacy, the ultimate goal for rational drug development, can only be achieved if direct analyses of the tissue cells in the actual human malignancy are analyzed. To that end, technologies such as Laser Capture Microdissection (LCM), is providing unparalleled access to the purified diseased human cells directly from tissue specimens. However, limited availability of patient material is a challenge towards the development of new highly sensitive proteomic methodologies. Two-dimensional gel electrophoresis (2D-PAGE), still the mainstay of most proteomic analysis of disease, is being complemented, and in some instances replaced by new exciting approaches to multiparametric protein characterization. The use of rapid, high throughput mass spectrometric-based fingerprints of peptides and proteins may prove to be valuable for new molecular classification of human tumors and disease stages. Coupled with LCM, high-density protein arrays, antibody arrays, and small molecular arrays, could have a substantial impact on proteomic profiling of human malignancies. Finally, detailed real-time knowledge about the states of intracellular signaling circuitry and pathways in the normal and malignant cells before, during and after therapy will yield invaluable information about mechanism of action and efficacy of existing and novel therapeutics for the treatment of human cancer.